Aesthetics as a space of difference: The implicit sociology in Tanizaki Jun’ichirō’s A Golden Death - Pierantonio Zanotti (Kervan. International Journal of Afro-Asiatic Studies, 2022)
Tanizaki Jun’ichirō’s short story Konjiki no shi (‘A golden death,’ 1914) tells the weird tale of a friendship between two young aspiring artists in early twentieth-century Japan. Watashi, the narrator, is a diligent student, has conventional ideas and becomes a conventional writer, while his friend Okamura, who is extremely wealthy and free to pursue his wildest ideas, develops to the most bizarre consequences his own original aesthetics based on the senses and the beauty of the human body.